1998
DOI: 10.1128/jcm.36.12.3731-3733.1998
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Resins in Neutralizing Antibiotic Activities in Bactec Plus Aerobic/F Culture Medium

Abstract: Incorporating resins in blood culture media can effectively reduce the activities of several antibiotics. It was shown that the activities of some generally used antibiotics decreased by 80 to 90% within 2 h in Bactec Plus Aerobic/F resin-containing culture medium. Bactec vials containing resins were still found to be positive for bacteria when antibiotics were present. The addition of β-lactamase shortened the detection time irrespective of the presence of resins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 20 publications
(24 reference statements)
0
16
0
1
Order By: Relevance
“…To minimize this risk, blood culture bottles containing proprietary binding resins that inactivate residual concentrations are available. However, these bottles and their binding resins perform differently based on the specific organisms and antimicrobials being combined (6)(7)(8)(9)(10). Lovern and colleagues observed differences in binding affinities for antibiotics across several classes, including ␤-lactams, fluoroquinolones, and glycopeptides, and these differences translated into the ability for BSI organisms to grow and be identified (11).…”
mentioning
confidence: 99%
“…To minimize this risk, blood culture bottles containing proprietary binding resins that inactivate residual concentrations are available. However, these bottles and their binding resins perform differently based on the specific organisms and antimicrobials being combined (6)(7)(8)(9)(10). Lovern and colleagues observed differences in binding affinities for antibiotics across several classes, including ␤-lactams, fluoroquinolones, and glycopeptides, and these differences translated into the ability for BSI organisms to grow and be identified (11).…”
mentioning
confidence: 99%
“…to prevent artificial sterilization of the sample (6)(7)(8)(9)(10)(11). In vitro and clinical studies have suggested variability in performances for different combinations of microorganisms, antibiotics, and binding systems (6)(7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…to prevent artificial sterilization of the sample (6)(7)(8)(9)(10)(11). In vitro and clinical studies have suggested variability in performances for different combinations of microorganisms, antibiotics, and binding systems (6)(7)(8)(9)(10)(11)(12). For example, Zadroga and colleagues (12) observed the recovery of Gram-negative bacteria in Becton Dickinson Bactec Plus BC bottles when piperacillin-tazobactam was administered prior to collection, while cultures from the same patients using bioMérieux BacT/Alert FAN bottles demonstrated residual piperacillin concentrations above the MIC, with no recovery.…”
mentioning
confidence: 99%
“…Culture media used with automated systems usually contain inhibitors for a broad range of antibiotics that reduce but do not eliminate the risk of false‐negative results 9,26‐29. In this context, the ratio of antimicrobial plasma in the inoculum as well as the delay between collection of the CB and inoculation of culture bottles must be taken into account by CB banks when validating their sterility method since these factors might reduce the survival of contaminating bacteria in tested CB samples and therefore contribute to false‐negative results.…”
Section: Discussionmentioning
confidence: 99%